Detektor Karbondioksida (CO2) Sebagai Pengaman Internal Mobil Berbasis Mikrokontroller - Moh Andre Kurniawan; Zainal Abidin; Arief Budi Laksono; Affan Bachri (Universitas Islam Lamongan, 2020)
Air is one of the kinds of the gas group as the main source of breathing for the living things. In the air, there are many types of gases, but not all of them are good to be inhaled, one of them is carbondioxide. Carbondioxide is mostly produced by the vehicles, and it is also present in the car. Carbondioxide detectoris a safety tool used in the car. It is based on microcontroller and can be used to provide security to its users. The MQ135 censor detects carbondioxideby transmitting the data through the ATMega328 microcontroller whose concentration can be viewed through the LCD. Actuators in this study consisted of LED, buzzer, and servo motors as the power windows drivers. When the carbondioxide gas level exceeds the threshold of 1000 ppm, the LED that originally is in green will turn into red, the buzzer will be active and the servo motor will move to open the power windows. Conversely, when the carbondioxide gas level has returned to normal, buzzer will turn off and automatically power windows will close with the help of servo motor, and LED will turn back into green. The set of tool that has been made, compared to the carbondioxide gas detector in the room resulting error value of 3.11%.